Light-Driven Metal-Free Direct Deoxygenation of Alcohols under Mild Conditions - Dawei Cao; Zhangpei Chen; Leiyang Lv; Huiying Zeng; Yong Peng; Chao-Jun Li (iScience, 2020)
Summary: Hydroxyl is widely found in organic molecules as functional group and its deprivation plays an inevitable role in organic synthesis. However, the direct cleavage of Csp3-O bond in alcohols with high selectivity and efficiency, especially without the assistance of metal catalyst, has been a formidable challenge because of its strong bond dissociation energy and unfavorable thermodynamics. Herein, an efficient metal-free strategy that enables direct deoxygenation of alcohols has been developed for the first time, with hydrazine as the reductant induced by light. This protocol features mild reaction conditions, excellent functional group tolerance, and abundant and easily available starting materials, rendering selective deoxygenation of a variety of 1° and 2° alcohols, vicinal diols, and β-1 and even β-O-4 models of natural wood lignin. This strategy is also highlighted by its “traceless” and non-toxic by-products N2 and H2, as readily escapable gases. Mechanistic studies demonstrated dimethyl sulfide being a key intermediate in this transformation.